a) F = ka + mx / - ka
F - ka = mx / : m
x = [tex]\frac{F - ka}{m}[/tex]
b) m = [tex]\frac{F}{a}[/tex] / * a
am = F / : m
a = [tex]\frac{F}{m}[/tex]
c) [tex]\frac{3 - x}{k}[/tex] = m / * k
3 - x = km / + x
3 = km + x / - km
x = 3 - km
d) V = [tex]\frac{1}{3}[/tex] PH / : [tex]\frac{1}{3}[/tex] P
H = [tex]\frac{V}{\frac{1}{3} P}[/tex]
e) s = [tex]\frac{at^2}{2}[/tex] / * 2
2s = at² / : at
t = [tex]\frac{2s}{at}[/tex]
f) w = [tex]\frac{m - M}{M}[/tex] * 100 / : 100
[tex]\frac{w}{100}[/tex] = [tex]\frac{m - M}{M}[/tex] / * M
[tex]\frac{w}{100}[/tex] * M = m - M / + M
m = [tex]\frac{w}{100}[/tex] * M + M